Sustainable Electroless Ni-P Deposition on Mild Steel with Natural Reductants from Lawsone - H. Asia Thabassoom; J. Felicita Florence (Recent Developments in Chemistry and Biochemistry Research Vol. 8, 2024)
This research investigates the effects of varying bath concentrations, operating temperature, and plating time on the electroless nickel deposition process using Lawsone extract from Lawsonia inermis. The study explores how complex agents and plating parameters influence the properties and structure of the deposited layer. The electroless nickel plating bath is optimized for environmental sustainability, utilizing NiSO4•7H2O as the primary salt. Preliminary findings suggest that the inclusion of a complex agent enhances the plating growth rate while maintaining an optimal pH of 6-8. The study highlights the potential for low phosphorus content, high density, and minimal porosity in the deposits, underscoring their excellent corrosion resistance. This work presents a novel, eco-friendly approach to nickel deposition with significant applications in industries requiring durable and corrosion-resistant coatings.